A film bulk acoustic resonator pressure sensor based on lateral field excitation. (November 2018) - Su, Shujing; Geng, Zihui; Ma, Xiaoxin; Tan, Qiulin; Xiong, Jijun
A high-sensitive thickness shear mode film bulk acoustic resonator pressure sensor based on lateral field excitation is designed with its structure simulated in environment of air and liquids. A finite element model of film bulk acoustic resonator pressure sensor structure is established to obtain frequency variation under different pressure conditions by parameter sweep method when the multi-physics fields are added to the model. The results of simulation show that the pressure sensor's resonance frequency is 2.114 GHz and pressure sensitivity is 1200 Hz/kPa in air. In liquid environment, film bulk acoustic resonator pressure sensor displays a pressure sensitivity of 325 Hz/kPa in ethanol, 475 Hz/kPa in deionized water, and 612.5 Hz/kPa in glycerol. This film bulk acoustic resonator pressure sensor has been proved to be highly sensitive both in air and liquid environment and has the potential to be used in biomedical applications.